(3GdeONd Edi GdLHGjI hGdVQGFH (B/s - (3eMQRj, eMeO YHGS s ((3GdLRGFQ (B: s (3OGQ GdfTQ(BITCIS, s)
(3jVe GdEWGQ GdeaGgjej ddVQjHI, GdJUfja GdJbfj ddVQGFH(B.s
(3HjHdjhZQGajG(B: (3U U(B.157-158s
Keywords: (3GdVQGFHs